ï¿¼USING INFORMATION AND COMMUNICATION ï¿¼TECHNOLOGY (ICT) TO ENHANCE LANGUAGE ï¿¼TEACHING & LEARNING: ï¿¼AN INTERVIEW WITH DR. A. GUMAWANG JATI - Flora Debora Floris (TEFLIN, 2014)
In recent years, information and communication technology (ICT) has become embedded and affected the every aspect of our lives. Rapid development of ICT has changed our language teaching pedagogy at all levels. Teachers, curriculum developers, researchers have been constantly striving to find techniques to use some form of it to both assist and enhance language learning. What is more exciting is that studies have demonstrated positive effects that ICT brings towards studentsâ learning motivation (Chenoweth, Ushida & Murday, 2006; Stepp- Greany, 2002), studentsâ personal needs and learning styles (Gimenez, 2000), studentsâ language mastery (Stepp-Greany, 2002), effective teaching and learning process (Al-Jarf, 2004), etc. Although these studies have shown that ICT has the potential important role in supporting and enhancing language learning, the use of ICT should never be the goal in and of itself. The responsibility for language instruction should be in the hands of qualified teachers who have the knowledge and expertise to manage and to make the best use of it to accomplish learning objectives. This interview highlights the issue of bringing ICT into the English language classrooms. Dr. A. Gumawang Jati, a senior lecturer at Faculty of Arts and Design, Bandung Institute of Technology (ITB) who specializes in the area of Technology and Education, was interviewed to share his experiences and insights on how ICT could be effectively used to support the language development process.Â